The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/09513590.2017.1296425
|View full text |Cite
|
Sign up to set email alerts
|

Serum visfatin, vascular endothelial growth factor and matrix metalloproteinase-9 in women with polycystic ovary syndrome

Abstract: Visfatin may induce the expression of pro-angiogenic factors, such as VEGF and MMP-9, in women with PCOS, inplying gradually development of endothelial dysfunction. Further studies are required to clarify these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 53 publications
2
13
0
Order By: Relevance
“…iNAMPT over-expression as well as increased circulating levels of eNAMPT were documented in metabolic/inflammatory conditions including obesity, type 2 diabetes, metabolic syndromes, atherogenic inflammatory diseases, therefore supporting a role for eNAMPT as a potential biomarker of cardio-cerebro-vascular disorders (157)(158)(159)(160). Enhanced eNAMPT levels are also described in kidney transplantation recipients (161), polycystic ovary syndrome (162), preeclampsia (163), and acute coronary syndrome (158,164). Increased eNAMPT levels were additionally reported in non-metabolic chronic inflammatory diseases [i.e., osteoarthritis (103) and acute lung injury (ALI) (165,166)], characterized by systemic inflammation.…”
Section: Nampt and Naprt As Biomarkers Of Chronic And Acute Inflammatmentioning
confidence: 89%
“…iNAMPT over-expression as well as increased circulating levels of eNAMPT were documented in metabolic/inflammatory conditions including obesity, type 2 diabetes, metabolic syndromes, atherogenic inflammatory diseases, therefore supporting a role for eNAMPT as a potential biomarker of cardio-cerebro-vascular disorders (157)(158)(159)(160). Enhanced eNAMPT levels are also described in kidney transplantation recipients (161), polycystic ovary syndrome (162), preeclampsia (163), and acute coronary syndrome (158,164). Increased eNAMPT levels were additionally reported in non-metabolic chronic inflammatory diseases [i.e., osteoarthritis (103) and acute lung injury (ALI) (165,166)], characterized by systemic inflammation.…”
Section: Nampt and Naprt As Biomarkers Of Chronic And Acute Inflammatmentioning
confidence: 89%
“…They showed that the serum level of MMP-9 was signi cantly higher in women with PCOS compared to the control group (42). The study of Dambala et al in 2017 also showed the same result (43). In the study of Javed et al (2913), the level of MMP-8 was higher in the saliva and serum of patients with PCOS and periodontal disease compared to the control group (comprised of women who were systemically healthy and had healthy gums) (16).…”
Section: Discussionmentioning
confidence: 75%
“…VEGF protein is known to be closely related to the pathogenesis of PCOS. Serum VEGF levels are significantly elevated in PCOS patients [16][17][18]. High levels of serum VEGF result in a higher number of active granuloas lutein cells (GLCs), increase secretion of GLCs, and up-regulate VEGF gene expression [40].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF), a homodimeric glycoprotein hormone first purified by Ferrara et al from the bovine pituitary follicular stellate cells in vitro, is the most active angiogenic factor ever known, which can maintain the differentiation state of vascular endothelial cells and improve microvascular permeability, and play a powerful regulatory role in the occurrence and development of various diseases [14,15]. It is closely related to the pathogenesis of PCOS, and studies have reported a significant rise in serum level of VEGF in the PCOS patients [16][17][18]. Additionally, the overexpression of VEGF gene in the polycystic ovarian stroma also reveals the critical role of this gene in the pathophysiology of PCOS [19].…”
Section: Introductionmentioning
confidence: 99%